2006
DOI: 10.1038/sj.emboj.7601411
|View full text |Cite
|
Sign up to set email alerts
|

Conditional deletion of Nbs1 in murine cells reveals its role in branching repair pathways of DNA double-strand breaks

Abstract: NBS1 forms a complex with MRE11 and RAD50 (MRN) that is proposed to act on the upstream of two repair pathways of DNA double-strand break (DSB), homologous repair (HR) and non-homologous end joining (NHEJ). However, the function of Nbs1 in these processes has not fully been elucidated in mammals due to the lethal phenotype of cells and mice lacking Nbs1. Here, we have constructed mouse Nbs1-null embryonic fibroblasts and embryonic stem cells, through the Cre-loxP and sequential gene targeting techniques. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
61
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 46 publications
9
61
1
Order By: Relevance
“…Previous studies have also shown that genetic disruption or kinase inhibition of DNA-PKcs, or genetic disruption of other c-NHEJ factors, cause an increase in the frequency of SSA (24,52); whereas disruption of another component of the MRE11-RAD50-NBS1 complex (NBS1) causes a decrease in SSA (37,65). As SSA requires extensive end processing to reveal the homology that flanks the DSB, these findings support the notion that c-NHEJ factors, including DNA-PKcs, are important to limit such extensive DSB end processing, whereas RAD50 and NBS1 promote this process.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that genetic disruption or kinase inhibition of DNA-PKcs, or genetic disruption of other c-NHEJ factors, cause an increase in the frequency of SSA (24,52); whereas disruption of another component of the MRE11-RAD50-NBS1 complex (NBS1) causes a decrease in SSA (37,65). As SSA requires extensive end processing to reveal the homology that flanks the DSB, these findings support the notion that c-NHEJ factors, including DNA-PKcs, are important to limit such extensive DSB end processing, whereas RAD50 and NBS1 promote this process.…”
Section: Discussionmentioning
confidence: 99%
“…Errorprone repair of the DSB by single strand annealing (SSA) is increased in BRCA2 mutants [87,88]-a pattern reminiscent of HR mutants in yeast and in other vertebrate cells. In contrast, SSA is partly dependent on BRCA1, suggesting that BRCA1 also participates in an earlier step in HR, perhaps working with the MRN complex to control processing of the DSB end [88,89]. These studies do not assay HR at stalled forks, since the induced DSB has no relation to replication arrest.…”
Section: Role Of Brca1 and Brca2 In Hr Regulationmentioning
confidence: 91%
“…MRX, the yeast orthologue of MRN, functions during NHEJ in the budding yeast Saccharomyces cerevisiae but not in the fi ssion yeast Schizosaccharomyces pombe ( 27 -29 ). In mammalian cells, MRN is not recruited to the site of DSBs generated by the I-sceI endonuclease in G1-phase cells, and MRN does not appear to be required for the NHEJmediated repair of these DSBs ( 30,31 ).…”
Section: Generation Of Nbs1 M/m and Mre11 Atld1/atld1 Abl Pre-b Cellsmentioning
confidence: 99%